Dose-Dense Epirubicin and Cyclophosphamide Followed by Docetaxel as Adjuvant Chemotherapy in Node-Positive Breast Cancer - Hamid Reza Mirzaei; Parisa Sabet Rasekh; Fatemeh Nasrollahi; Parto Sabet Rasekh; Zahra Akbari Tirabad; Hamid Reza Moein; Taban Ghaffari Pour; Parastoo Hajian (International Journal of Breast Cancer)
Background. Adding taxanes to anthracycline-based adjuvant chemotherapy has shown significant improvement particularly in node-positive patients, but optimal dose and schedule remain undetermined. Objectives. This study aimed to assess the feasibility of dose-dense epirubicin and cyclophosphamide followed by docetaxel in node-positive breast cancer. Methods. All Patients first received 4 cycles of epirubicin (100 mg/m2) and cyclophosphamide (600 mg/m2) at 2-week interval then followed by docetaxel (100 mg/m2) at 2-week interval for 4 cycles, with daily Pegfilgrastim (G-CSF) that was administered in all patients on days 3–10 after each cycle of epirubicin and cyclophosphamide infusion. Results. Fifty-eight patients with axillary lymph node-positive breast cancer were enrolled in the study, of whom 42 (72.4%) completed the regimen. There were two toxicity-related deaths, one patient due to grade 4 febrile neutropenia and the other due to congestive heart failure. Grade 3/4 neutropenia and febrile neutropenia were 13.8% and 5.1%. The most common grade 3/4 nonhematological complications were as follows: skin-nail disorders (48.3%), hand-foot syndrome (34.4%), paresthesia (38%), arthralgia (27.5%), and paresis (24.1%). Conclusions. Dose-dense epirubicin and cyclophosphamide followed by docetaxel with G-CSF support are not feasible, and it is not recommended for further investigation.